Grassland association stock of plants the examination of the regeneration of a construction - Varga, Krisztina; Csízi, István (Acta Agraria Debreceniensis, 2024)
Due to the drastic change in using the nature like grassland association (one-sided overgrazing – one mowing per a year), by the third year of the experiment in every area, where overgrazing stopped, independently on second sowing and nutrient resupply, Borhidi degradation degree decreased. In the areas where overgrazing with large animal density (sheep) continued, degradation degree was 3.4–5.0 by the third year of the experiment, and Hordeum murinum, which causes animal healthy problems, appeared massively.